2014
DOI: 10.4331/wjbc.v5.i4.457
|View full text |Cite
|
Sign up to set email alerts
|

Short- and long-term effects of silver nanoparticles on human microvascular endothelial cells

Abstract: croscope. RESULTS:Ag NP are cytotoxic in a dose and time dependent fashion for HMEC. At high concentrations, Ag NP determine loss of membrane integrity as demonstrated by the increased activity of lactate dehydrogenase in the culture medium. Ag NP rapidly stimulate the formation of free radicals. However, pre-incubation with Trolox, apocynin, or N-acetyl-L-cysteine, antioxidants which have different structure and act through different mechanisms, is not sufficient to prevent cytotoxicity. Ag NP also induce DNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 28 publications
2
46
0
1
Order By: Relevance
“…Several studies have reported the toxicity of Ag NP in different cell systems both in vitro and in vivo [6][7][8]. Consequently, the possibility to exploit their cytotoxic activity to treat proliferative diseases is particularly challenging.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have reported the toxicity of Ag NP in different cell systems both in vitro and in vivo [6][7][8]. Consequently, the possibility to exploit their cytotoxic activity to treat proliferative diseases is particularly challenging.…”
Section: Discussionmentioning
confidence: 99%
“…Ag and AgPVP NP (NanoAmor, Houston, USA) were previously used [8]. Briefly, Ag NP are 99.5% pure with an average particle size of 35 nm.…”
Section: Reagentsmentioning
confidence: 99%
See 1 more Smart Citation
“…It could be that these observations are influenced by AuNP concentrations and culture time. Most studies focus on the short term acute effects of AuNP exposure but long term culture with AuNPs could change gene expressions levels and cell behavioral responses [30,31]. Hence it is also important to investigate such exposure especially as AuNPs are being put to use for long term clinical applications [32,33].…”
Section: Functional Group Effect On Hmsc Behavior and Differentiationmentioning
confidence: 98%
“…The idea of reversibility is in conformity with the observation of others that upon exposure of sublethal concentrations of AgNPs for long times, cells remained viable and their growth retarded. Similarly, genotoxicity was found to be reversible upon removal of AgNPs from cell culture [30], suggesting that chromatin changes are not permanent. However, extended regeneration time associated with the treatment of higher concentrations (160, 320 ppm) of large AuNP particles could raise concern about smaller (<100 nm) nanogold particles that could be toxic alone or in combination with experimental drugs.…”
Section: Resultsmentioning
confidence: 99%